2022
DOI: 10.47750/pnr.2022.13.s03.282
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of SCoT, ISSR, and SRAP markers for detecting genetic polymorphism among Egyptian barley genotypes

Abstract: The results of the present study support the idea that, the tested Egyptian barley cultivars could make a useful case study for genetic diversity research. When those cultivars were examined using three distinct markers (codon targeted (SCoT), sequence-related amplified polymorphism (SRAP) and inter-simple sequence repeats (ISSR)). According to SRAP, ISSR, and SCoT analyses, respectively 85, 76, and 66 polymorphism percentages among the seven tested barley cultivars were detected. The genotype specific markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…In this study, 10 SCoT primers in particular showed a total of 94 fragments, 29 of which were monomorphic, and 65 bands, or 62.18% (polymorphism), of which 21 were unique bands (9 positive specific markers and 12 negative specific markers). For examining the genetic divergence between barley types, prior investigations used SCoT markers, which showed between 66.67 and 100% polymorphism [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 10 SCoT primers in particular showed a total of 94 fragments, 29 of which were monomorphic, and 65 bands, or 62.18% (polymorphism), of which 21 were unique bands (9 positive specific markers and 12 negative specific markers). For examining the genetic divergence between barley types, prior investigations used SCoT markers, which showed between 66.67 and 100% polymorphism [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%